Dilated intercellular spaces of esophageal epithelium in non- erosive reflux disease: Transmission electron microscopic (TEM) study - Myint, Yi Yi; Tun, Ye; Mohammad Amjad, Nasser; Mat Hassan, Mohd. Zailani; Abdul Rashid, Nor Linda (Universiti Putra Malaysia, 2011)
The prevalence of Non-erosive reflux disease (NERD) is increasing in Asia. Dilated intercellular spaces (DIS) are considered as early signs of acid damage to the esophageal epithelium. There is little information available in the literature on the (DIS) of esophageal epithelium in NERD patients in Malaysia. The aim of this study is to evaluate DIS of Malaysian patients with NERD and normal controls. The study group included 8 patients with reflux symptoms, normal mucosa on endoscopy and positive 24-hour pH monitoring and 5 normal controls. Specimens were taken 5 cm above the Z line during endoscopy. The biopsies were routinely processed for transmission electron microscopy (TEM). Morphometric analysis on microphotographs showed that mean intercellular space diameter values of NERD patient was significantly higher than normal controls (p<0.001). The maximal value of the mean intercellular spaces in controls and NERD were 0.44 μm and 1.13 μm respectively. There was no overlap between the two values, so the intermediate value 0.93 μm was considered as cut-off value. DIS at prickle cell layer is a promising diagnostic marker of early damage of esophageal epithelium.